Comparison of hand-eye and dominance visual reaction time in swimmers. - Balcı, Aydın; Baysal, Seda; Kabak, Banu; Akınoğlu, Bihter; Kocahan, Tuğba; Hasanoğlu, Adnan (Spor Hekimligi Dergisi/Turkish Journal of Sports Medicine, 2021)
Objective: The aim of this study is to compare visual reaction times of swimmers with similar or different side dominance of the hand and eye. Material and Methods: Thirty regularly training swimmers were included in the study. Hand dominance was based on answers given to specific questions; eye dominance was determined by the eye lateralization test. Athletes with right hand dominance were divided into two groups with right side eye dominance (straight dominant), and left side eye dominance (counter dominant). Visual reaction times of swimmers were evaluated with the Witty-Sem © visual reaction test device. Data were compared between groups using the Mann Whitney-U test. Different visual reaction times within the group were evaluated using the Friedman chi-square test, and origin of any significant difference was determined with the Wilcoxon signed sum of ranks test. Statistical error level was set at p<0.05. Results: There was no significant difference between the visual reaction times of straight- and counter dominant swimmers (p>0.05). Straight-dominant athletes had different reaction times for both hands with the right or left eye open, and the right hand with both eyes open. Right hand reaction time with the left eye open was the shortest, and left hand reaction time with the right eye open was the longest (X2(2)=20,455, p=<0.001). It was determined that the openness of the right or left eye and the hand used did not affect reaction time in cross-dominant athletes (X2(2)=7,773, p=0.102). Conclusions: There was no difference between the visual reaction times of swimmers with and without the dominant eye and hand on the same side. It was determined that right-hand reaction time when the left eye was open was shorter in swimmers with similar side eye and hand (right) dominance. In sports branches where visual reaction is important, this assessment may be beneficial in athlete selection and performance improvement.